Knowledge and Achievement Motivation of Marine Fishers : A Case of Alternate Livelihood Options in Tamil Nadu - Johnson, B., A. K. Abdul Nazar and R. Narayanakumar, (Indian Journal of Extension Education, 2017)
In recent past, farming of marine fishes is being encouraged among the marine fishers to supplement the householdincome from capture fisheries, because the fish catch is declining. The study on extent of knowledge and achievementmotivation of marine fishers’ adopting alternate livelihood options like sea cage farming, seaweed farming andornamental fish culture was conducted in Ramanathapuram district of Tamil Nadu since many marine fisheries relatedactivities are being undertaken in larger scale in comparison to other coastal districts. Overall analyses on level ofachievement motivation reveal that majority of respondents who are adopting the alternate livelihood options are havingmedium to high level of achievement motivation. All the farming options have to be undertaken in the sea, which is acommon property and it demands a common consensus in a particular village or region for taking up an activity in adesirable and profitable way. Hence, the need for personal achievement was present in majority of fishers, followed bypersonal achievement oriented influence and need for social achievement. The study found that fishers were able toperform better in the knowledge test since they gained adequate knowledge on all the alternate livelihood options.